Environmentally conscience corrosion inhibitors for mild steel in corrosive hydrochloric acid solution by Uncaria Cordata extract: experimental and theoretical studies - Othman, Nor Affanizam; Marwan Ali, Ab Malik; Samsia, Noor Syafiqah; Salim, Fatimah; Dedikarni Panuh, Dedikarni Panuh; Yaakob, Muhamad Kamil; Zaidi Embong, Zaidi Embong; Md Sauri, Ahmad Shalabi; Che Isa, Nik Norziehana; Nor Hashim, Nor Zakiah (Taylor&francis, 2023)
The Uncaria Cordata as corrosion inhibitors for mild steel (MS) in a 1.0 M hydrochloric acid (HCl) solution. The EIS, polarization, and LPR measurements were used as experimental measurements to confirm the anti-corrosion performances of the Uncaria Cordata at room temperature. The corrosion inhibitors, even at a low dosage range, achieved inhibition efficiencies to a maximum of 97.0% for 400 ppm of Uncaria Cordata. Surface morphology via AFM and SEM/EDX was carried out to validate the presence of protected film and an optimum concentration of each extract above the metal’s surface in the corrosive acidic solution. The DGo ads value 19.70 kJ/mol proved a spontaneous merge of physical and chemical adsorption by the extract compounds at the interface of MS and the HCl solution. DFT was governed to accommodate the elevated inhibition efficiency upshot obtained by the electrochemical tests and recommend a synergy mechanism for most of the adsorbed active compounds in Uncaria Cordata inhibitors with the MS surface. Monte Carlo simulation indicates three active compounds, namely 1, 2, and 8, found to have parallel adsorption on MS. This encourages the highest surface coverage and shields the MS surface from the intrusion of corrosive agents.